UJI VALIDITAS DAN RELIABILITAS ANGKET KEPERCAYAAN DIRI - Putri Rindiasari Rindiasari, Hidayat, Yuliani; Wahyu Hidayat; Wiwin Yuliani (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
This research is motivated by the existence of self-confidence problems that occur in students. Self-confidence has an important role for all individuals, especially in the field of education, self-confidence is a person's basic capital in meeting their own various needs. Every student must have self-confidence to know the abilities that exist in him and develop the potential that is in him. Therefore, a confidence measurement tool is needed in the form of a confidence questionnaire that has been tested for validity and reliability. From 50 statement items, 10 statements are obtained that are declared valid and the validity test gets a value of 0.446 which is included in the moderate category. That way self-confidence questionnaires can be used with shifting results when used with other subjects. Keywords:  Self Confidence, Validity, Reliability